Finansowanie rozwoju budownictwa mieszkalnego z (zasobów) Krajowego Funduszu Mieszkaniowego - Majczyna, Alina (Housing construction development financing from the (resources of) National Housing Fund, 2007)
The National Housing Fund (KFM) has been operating since 1996. The Funds' main tasks include the support of the programme of social housing construction for rent, namely financing at reasonable rents. Preferential credits arc granted to Social Housing Construction Societies and housing cooperatives. These credits may be designated for the construction, exlention. And adaptation of buildings with the Oats assigned for rent or cooperative tenancy housing. Preferential credits are also granted from KFM funds to municipalities for financing the technical infrastructure accompanying housing cooperation. The structure of the KFM credit portfolio is dominated by credits extended to Social Housing Construction Societies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 63-75